Bioefficacy of hydromethanolic extract of tuber of Chlorophytum borivilianum (Safed Musli) for the management of male infertility in cyproterone acetate‐treated albino rats. (19th August 2013) - Ray, S.; Chatterjee, K.; De, D.; Ghosh, D.
Summary Increase in male sexual dysfunction, and its treatment with conventional aphrodisiac drugs with side effects lead to investigate the spermatogenesis and androgenesis augmentative efficacy of hydromethanolic (40 : 60) extract of root of Chlorophytum borivilianum (family – Liliaceae) against cyproterone acetate‐induced subfertility in Wistar strain male albino rat. For this purpose, experimental rats were divided into three treatment groups: vehicle (received distilled water), cyproterone acetate (gastric intubation at 250 mg kg−1 twice daily for 35 days) and cyproterone acetate plus root extract of C. borivilianum (gastric intubation at 250 mg kg−1 plus 400 mg kg−1 with an interval of 20 min twice daily for 35 days). After 35‐day treatment, all rats were euthanised. Reproductive deviations towards negative side were investigated by screening the spermatogenic and steroidogenic biosensors. Oxidative stress profile in reproductive organs and sperm pellet was evaluated by biochemical assessment of antioxidative enzyme activities and level of end products of the lipid peroxidation. Apoptosis profile was evaluated by Western blot study, TUNEL assay and DNA fragmentation study of testicular tissues. Evaluation of toxicity profile was included for experimental investigation. After cyproterone acetate treatment, the pituitary–testicular axis was deviated towards the negative side and its tuning system was affected by oxidative stress and apoptosis‐mediated process, which reduced the quality of semen and finally led to subfertility. Co‐administration of C. borivilianum root extract enhanced male reproductive potentiality and prevented the negative deviations after the treatment with cyproterone acetate by means of increasing oxidative defence and maintaining homeostasis in testicular apoptosis process.